2021
DOI: 10.1155/2021/5516035
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulatory Effect of the Gut Microbiota in Kidney Disease

Abstract: The human gut microbiota is a complex cluster composed of 100 trillion microorganisms, which holds a symbiotic relationship with the host under normal circumstances. Intestinal flora can facilitate the treatment of human metabolic dysfunctions and interact with the intestinal tract, which could influence intestinal tolerance, immunity, and sensitivity to inflammation. In recent years, significant interests have evolved on the association of intestinal microbiota and kidney diseases within the academic circle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 155 publications
(190 reference statements)
0
49
0
Order By: Relevance
“…However, it also reduces the injurious effect of several kidney diseases, including diabetic nephropathy, glomerulonephritis, chronic renal failure, and acute kidney injury [ 424 , 425 , 426 , 427 ]. Similarly, intestinal flora has been reported to prevent the development and progression of several renal diseases, such as lupus nephritis, chronic kidney disease, diabetic nephropathy, and renal ischemia–reperfusion injury [ 428 ]. Similarly, both taurine and gut bacteria play a role in cardiovascular diseases [ 429 , 430 ], neurological [ 51 , 53 , 54 , 55 , 56 , 57 , 58 , 60 , 61 , 62 , 63 , 64 , 431 ] and multiple other disorders.…”
Section: Taurine In the Context Of Bas And Microbiotamentioning
confidence: 99%
“…However, it also reduces the injurious effect of several kidney diseases, including diabetic nephropathy, glomerulonephritis, chronic renal failure, and acute kidney injury [ 424 , 425 , 426 , 427 ]. Similarly, intestinal flora has been reported to prevent the development and progression of several renal diseases, such as lupus nephritis, chronic kidney disease, diabetic nephropathy, and renal ischemia–reperfusion injury [ 428 ]. Similarly, both taurine and gut bacteria play a role in cardiovascular diseases [ 429 , 430 ], neurological [ 51 , 53 , 54 , 55 , 56 , 57 , 58 , 60 , 61 , 62 , 63 , 64 , 431 ] and multiple other disorders.…”
Section: Taurine In the Context Of Bas And Microbiotamentioning
confidence: 99%
“…Gut microbiota dysbiosis contributes to the impaired gut barrier, excessive production of uremic toxins, and translocation of the gut microbiome, leading to the abnormal activation of the immune cells [62]. The active immune cells, such as neutrophils, macrophages, dendritic cells, and lymphocytes, then infiltrate kidneys and promote the pro-or antiinflammatory reactions [60].…”
Section: Immunomodulatory Mechanisms Of Gut Microbiota In Ckdmentioning
confidence: 99%
“…Gut dysbiosis affecting the integrity of the intestinal barrier may lead to bacterial translocation, production, and accumulation of dysbiotic gut-derived metabolites, such as urea, indoxyl sulfate, and p-cresyl sulfate, which cause abnormal activation of immune cells, overproduction of antibodies, immune complexes, and inflammatory factors that may directly or indirectly cause damage to the renal parenchyma [ 38 ]. Administration of the probiotic L. casei has been shown to reduce kidney inflammation by restoring the SCFA-producing gut microbiome and nicotinamide metabolism [ 39 ]. Regulating the gut microbiome has been shown to lower blood pressure, ameliorate kidney disease, and prevent complications in patients with chronic kidney disease.…”
Section: Kidney Regenerationmentioning
confidence: 99%
“…Studies have shown the correlation between intestinal flora and diabetes. Restoring the gut microbiota is considered to be an effective strategy in preventing and treating diabetes and diabetic nephropathy [ 39 ]. Administration of antibiotics has been shown to protect against renal ischemia-reperfusion injury by reducing the maturation status of the bone marrow monocytes and F4/80 + renal resident macrophages [ 39 ].…”
Section: Kidney Regenerationmentioning
confidence: 99%